Impact of high Spirulina diet, extruded or supplemented with enzymes, on blood cells, systemic metabolites, and hepatic lipid and mineral profiles of broiler chickens - Spínola, Maria P.; Alfaia, Cristina M.; Costa, Mónica M.; Pinto, Rui M. A.; Lopes, Paula A.; Pestana, José M.; Tavares, João C.; Mendes, Ana R.; Mourato, Miguel P.; Tavares, Beatriz; Carvalho, Daniela F. P.; Martins, Cátia F.; et al. (Frontiers in Veterinary Science, 2024)
The impact of 15% dietary inclusion of Spirulina (Arthrospira platensis) in broiler chickens was explored, focusing on blood cellular components, systemic metabolites and hepatic lipid and mineral composition. From days 14 to 35 of age, 120 broiler chickens were divided and allocated into four dietary treatments: a standard corn and soybean meal-based diet (control), a 15% Spirulina diet, a 15% extruded Spirulina diet, and a 15% Spirulina diet super-dosed with an enzyme blend (0.20% porcine pancreatin plus 0.01% lysozyme). The haematological analysis revealed no significant deviations (P > 0.05) in blood cell counts across treatments, suggesting that high Spirulina inclusion maintains haematological balance. The systemic metabolic assessment indicated an enhanced antioxidant capacity in birds on Spirulina diets (P < 0.001), pointing towards a potential reduction in oxidative stress. However, the study noted a detrimental impact on growth performance metrics, such as final body weight and feed conversion ratio (both P < 0.001), in the Spirulina-fed treatments, with the super-dosed enzyme blend supplementation failing to alleviate these effects but with extrusion mitigating them. Regarding hepatic composition, birds on extruded Spirulina and enzyme-supplemented diets showed a notable increase in n-3 fatty acids (EPA, DPA, DHA) (P < 0.001), leading to an improved n-6/n-3 PUFA ratio (P < 0.001). Despite this positive shift, a reduction in total hepatic lipids (P = 0.003) was observed without a significant change in cholesterol levels. Our findings underscore the need for further exploration into the optimal inclusion levels, processing methods and potential enzymatic enhancements of Spirulina in broiler diets. Ultimately, this research aims to strike a balance between promoting health benefits and maintaining optimal growth performance in poultry nutrition.